Rekognisi Pemberdayaan Ekonomi Masyarakat Berbasis Zakat Community Development di Lembaga Amil Zakat Al-Azhar Surabaya - Basar Dikuraisyin; Firda Adilah Dewi (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2021)
We cannot underestimate the potential of ZISWAF funds (Zakat, Infaq, Alms, and Waqf) among Muslims in Indonesia. In the last 10 years, almost all of the emergence of ZISWAF management and channeling agencies in Indonesia have transformed itself into a new business competition. Many factors cause or underlie the emergence of ZISWAF management institutions which are quite complex. Besides the significant economic growth and the religious awareness of the Muslim middle class and above, the management of ZISWAF funds in Indonesia is still classified as traditional. The purpose of writing this journal is to find out about how zakat managers utilize the existing ZISWAF funds for people who need them and of course, they are right on target. So that later there will be many people or muzakki who believe that the funds they have provided are well managed by the zakat management institution. In addition, another goal is for the community to feel the impact of this empowerment so that the community can be more effective, for example with this empowerment program, where initially the community could not develop the skills they had with the assistance and training from this program, the community would later more able to generate their income. That way the unemployment rate and poverty in the community will be slightly reduced.